Design of Architectures and Materials in In‐Plane Micro‐supercapacitors: Current Status and Future Challenges - Qi, Dianpeng; Liu, Yan; Liu, Zhiyuan; Zhang, Li; Chen, Xiaodong (Advanced materials (Weinheim), 2017)
The rapid development of integrated electronics and the boom in miniaturized and portable devices have increased the demand for miniaturized and on‐chip energy storage units. Currently thin‐film batteries or microsized batteries are commercially available for miniaturized devices. However, they still suffer from several limitations, such as short lifetime, low power density, and complex architecture, which limit their integration. Supercapacitors can surmount all these limitations. Particularly for micro‐supercapacitors with planar architectures, due to their unique design of the in‐plane electrode finger arrays, they possess the merits of easy fabrication and integration into on‐chip miniaturized electronics. Here, the focus is on the different strategies to design electrode finger arrays and the material engineering of in‐plane micro‐supercapacitors. It is expected that the advances in micro‐supercapacitors with in‐plane architectures will offer new opportunities for the miniaturization and integration of energy‐storage units for portable devices and on‐chip electronics. In‐plane micro‐supercapacitors possess the merits of easy fabrication and integration into on‐chip electronics, and offer new opportunities for the miniaturization and integration of energy‐storage units for portable devices. Strategies to fabricate electrode finger arrays and the material engineering of in‐plane micro‐supercapacitors are discussed.